Elements of an effective accounting information system - Torres Gallardo, Arturo (2019)
The accounting information systems, whether these are manual or computerized systems, determine the level of coupling and interaction.  This is a crucial task in the analysis stage if you want to design an accounting information system that after its implementation is effective. We identified the main components of the accounting information system, such as the business line, the business processes, the technical-accounting standards, the chart of accounts, the personnel, the accounting policies, the organization chart, the pattern of operations, the manual of functions, the manual of accounting procedures, the books or system of accounting records, the forms or documentation, the internal control, the software, the hardware, the reports and financial reports. The main components, both internal and those of the environment, are in permanent interaction and constitute forces that interact with the organization directly affecting the operation of the accounting information system. Although they do not represent all of them, nor do they have the same relevance in all types of companies, but the level of coupling between them is very important and directly affects the accounting information.